Formulasi dan Karakterisasi Nanopartikel Ekstrak Biji Carica (Carica pubescens) dengan Variasi Konsentrasi Kitosan menggunakan Metode Gelasi Ionik - Fania Putri Luhurningtyas; Prashinta Nita Damayanti; Suzan Astyamalia; Mir-a Kemila; Evi Novitasari (UIN Syarif Hidayatullah Jakarta, 2024)
Carica seeds (Carica pubescens) contain alkaloid, saponin, and flavonoid compounds, which have pharmacological activities such as antibacterial, anti-inflammatory, immunomodulatory, and antihyperlipidemic properties, but their bioavailability is low. Nanotechnology has significantly advanced in drug delivery systems because it can enhance absorption in the gastrointestinal tract, allowing entry into the bloodstream. This study aims to create and evaluate the characteristics of carica seed extract nanoparticles with varying concentrations of chitosan. The carica seed extract was obtained using the maceration method with 70% ethanol as the solvent. The Carica seed extract was then formulated into nanoparticles using the ionic gelation method with varying concentrations of chitosan: NaTPP, specifically formulas FA (0.3:1), FB (0.2:1), and FC (0.1:1). The resulting nanoparticle colloids were characterized for particle size, polydispersity index (PDI), percent transmittance (%T), and specific functional groups. The results showed that the particle sizes for formulas FA, FB, and FC were 243.7 nm, 47.96 nm, and 116.6 nm, respectively. The PDI values for formulas FA, FB, and FC were 0.378, 0.357, and 0.52, respectively. The percent transmittance for all three formulas ranged from 99.5% to 99.6%. The characterization of functional groups indicated interactions between the carica seed extract, chitosan, and NaTPP, with the presence of OH, N-H, aliphatic CH, P=O, and PO3 groups. These interactions were observed based on the shift in wavenumbers in the FTIR results for each sample. All carica seed nanoparticle formulas showed particle sizes within the nanometer range (<1000 nm), polydispersity indices less than 1, percent transmittance close to 100%, and specific functional groups indicating interactions between the extract and the coating polymer. Formula FB was the optimal formula, with the smallest nanoparticle size (<100 nm), a PDI value of <0.5, and a percent transmittance of >99%.